The Chinese Government's formal institutional influence on corporate environmental management - Rowe, Anna; Guthrie, J. (Routledge, 2010)
This article reports on part of a larger empirical study examining senior managers' perceptions of corporate environmental management (CEM) and reporting in China. ‘Coercive government institutional involvement’ emerged as one of the major influencing themes of CEM. The state regulatory regime has been perceived by Chinese managers to be the most influential, most complex and least predictable in terms of organizational environmental performance. The study found that environmental management systems that work in developed nations should not be directly transplanted to developing nations without considering institutional contexts. Notwithstanding China's dynamic economic boom and modernization, the State still exerts institutional influence on CEM.